2011
DOI: 10.1111/j.1756-185x.2011.01687.x
|View full text |Cite
|
Sign up to set email alerts
|

Distinct impacts of syndesmophyte formation on male and female patients with ankylosing spondylitis

Abstract: AS patients with syndesmophytes experienced imbalance of bone metabolism due to inflammatory cytokine release. Male AS patients had high levels of bone resorption markers, cytokines and adhesion molecules, reflecting a disorder of bone metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 14 publications
3
21
0
Order By: Relevance
“…On the other hand, a significantly higher proportion of men with AS reported hypertension compared with women. Sex differences as observed in our analysis have been discussed in other studies, highlighting that women may manifest AS differently than men due to different immunologic [22, 23] and genetic [24, 25] responses to the disease. Additionally, enthesitis [2628] and disease severity [29, 30] were significantly more pronounced in women with AS compared with men in several studies [2932].…”
Section: Discussionsupporting
confidence: 64%
“…On the other hand, a significantly higher proportion of men with AS reported hypertension compared with women. Sex differences as observed in our analysis have been discussed in other studies, highlighting that women may manifest AS differently than men due to different immunologic [22, 23] and genetic [24, 25] responses to the disease. Additionally, enthesitis [2628] and disease severity [29, 30] were significantly more pronounced in women with AS compared with men in several studies [2932].…”
Section: Discussionsupporting
confidence: 64%
“…Most scholars believe that this disease is an autoimmune inflammation reaction caused predominantly by genetic factors, in addition to being stimulated by trauma, infection, fatigue and other environmental factors (25)(26)(27). The present results showed that naringin attenuates NF-κB p65 unit, TNF-α, IL-1β and IL-6 activity in AS mice.…”
Section: A B a Bsupporting
confidence: 65%
“…Specifically, we show that Th1 cell polarization is skewed in patients with AS. Serum IFNg levels are higher in AS patients compared with those in controls; however, the levels in male and female patients are equivalent, as previously reported (19). Additionally, flow cytometric analysis demonstrated a reduction in the number of IFNg1CD41 T cells (Th1 cells), reminiscent of the "reverse IFNg profile" seen in humans and HLA-B27-transgenic rats (20)(21)(22).…”
Section: Discussionsupporting
confidence: 53%